Employment Generation Challenges and Strategies for Pakistan: A Diagnostic Analysis - Begum, Azeema (Unisia, 2022)
The employment challenges are getting more complex and worse because youth under the age of 30 constitute 64 percent of the total population. The gradual increase in labor force participation is adding more pressure to the labor market to generate employment opportunities. Hence, the growth in employment generation is essential to match the unprecedented number of young people entering working age in Pakistan. Moreover, the structural transition process involving labor movement from low-to-high productive activities has been much slower in Pakistan than in other Asian countries like China. This study identifies all major concerns regarding employment challenges in Pakistan and identifies various strategies and policies while adopting a diagnostic approach to employment policy. The reason for adopting the diagnostic approach/framework is to develop an understanding of the factors which are responsible for the slow growth of employment in formal sectors and significant constraints for generating more employment. It attempts to assess various elements that may find a place in developing strategies and policies. While designing effective policies for employment, policymakers must consider all aspects like population, demographics, types of unemployment, economic condition, social structure, and development stage of a country. Meanwhile, the role of entrepreneurial activities and the private sector, technological changes, development of labor-intensive industries and SMEs, improving skills and knowledge, youth employment programs, active labor market policies (ALMPs), and macroeconomic policies are core elements that should be considered to design effectual policies for employment generation.